KANDUNGAN BAHAN ORGANIK PADA SEDIMEN DI PERAIRAN TELUK BUYAT DAN SEKITARNYA - Manengkey, Hermanto WK (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2010)
Information on water conditions, such as sedimentation, physical factors, and coral reef ecosystem, needs to be understood that the stakeholders could optimally utilize the the area. This study was aimed to measure the organic content in the sediment content of Buyat Bay and its surroundings. Results found that the terrestrial sediments had higher percentage than from the surrounding waters.